Sovereign Risk and Financial Risk - Simon Gilchrist; Bin Wei; Vivian Z. Yue; Egon Zakrajések (Federal Reserve Bank of Atlanta, 2021)
In this paper, we study the interplay between sovereign risk and global financial risk. We show that a substantial portion of the comovement among sovereign spreads is accounted for by changes in global financial risk. We construct bond-level sovereign spreads for dollar-denominated bonds issued by more than 50 countries from 1995 to 2020 and use various indicators to measure global financial risk. Through panel regressions and local projection analysis, we find that an increase in global financial risk causes a large and persistent widening of sovereign bond spreads. These effects are strongest when measuring global risk using the excess bond premium, which is a measure of the risk-bearing capacity of US financial intermediaries. The spillover effects of global financial risk are more pronounced for speculative-grade sovereign bonds.
Keywords: E43; E44; F33; G12; 330; sovereign bonds; CDS; global financial risk; excess bond premium; global financial cycle